Peningkatan Literasi Dagang UMKM Ekspor: Sosialisasi Strategi Digitalisasi dan Diversifikasi Pasar di Tengah Kebijakan Tarif Resiprokal - Yuliani Almalita; Rinjani Rinjani (Yayasan Literasi Sains Indonesia, 2025)
Micro, small, and medium enterprises (MSMEs) in Indonesia are facing significant pressure due to reciprocal tariff policies that have emerged as a result of the trade war between the United States and its trading partners. The increase in tariffs on Indonesian export products has reduced the competitiveness of MSMEs in international markets and hindered the sector’s contribution to foreign trade. This activity aims to analyze the impact of reciprocal tariff policies on export-oriented MSMEs and to formulate adaptive strategies that can strengthen their competitiveness amid changes in global trade policies. The program was carried out as a Community Service Activity (PkM) through online dissemination, focus group discussions, and awareness-building sessions conducted during “The International Multidisciplinary Community Service Activity,” organized by the Association of Community Service Lecturers of Indonesia (ADPI). Participants included export-oriented MSME actors and the general public who collaborated in discussing market diversification and business digitalization strategies as adaptive measures to address reciprocal tariff policies. The results showed an increase in participants’ international trade literacy, understanding of adaptive export strategies, and the establishment of collaboration between academics and business actors. The conclusion of this activity emphasizes that continuous support through training, fiscal incentives, and deregulation is essential for MSMEs to survive and enhance their competitiveness amid the challenges posed by reciprocal tariff policies.